2006
DOI: 10.1111/j.1600-0714.2006.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of betel chewing, tobacco smoking and alcohol consumption on oral submucous fibrosis: a case–control study in Sri Lanka

Abstract: The present study has shown a strong association of betel quid chewing (including tobacco as an ingredient) with the causation of OSMF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 17 publications
4
43
0
Order By: Relevance
“…The habit of betel quid chewing is implicated in the high prevalence of oral cancer in these countries. Betel quid consists of a mixture of fresh areca nut, slaked lime from seashells, fresh betel leaf and partially dried tobacco (2)(3)(4). The association of these components with oral carcinogenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The habit of betel quid chewing is implicated in the high prevalence of oral cancer in these countries. Betel quid consists of a mixture of fresh areca nut, slaked lime from seashells, fresh betel leaf and partially dried tobacco (2)(3)(4). The association of these components with oral carcinogenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is most common in persons aged 20-40 years with a peak incidence of 29.09 years (4) and male: female ratio of 34:1 (7). It is a collagen disorder which leads to fibroelastic changes in the oral mucosa leading to limited access to the oral cavity, and it compromises oral hygiene and even food intake (1). Onset of OSMF is insidious over a 2-5 year period (8).…”
Section: Introductionmentioning
confidence: 99%
“…Oral submucous fibrosis (OSMF) is a disabling, chronic, insidious potentially malignant condition of the oral cavity seen predominantly in the Indian subcontinent (1)(2)(3). The prevalence rate of OSMF in India is considered to be 0.2-0.5% (4).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Masseter Muscle thickness increases as the duration and frequency of the habit increase (12) . Thick inelastic circumoral fibrous bands around the entire circle of lips could result in thinning of lips and narrowing of rimaoris leading to difficulty in mouth opening (13) . The other findings of exaggerated malar prominence, multiple shallow nasolabial folds and Pseudo-proptosis (appearance of bulged eyeballs) were relatively uncommon in our series, but nevertheless we believe that when these features are present together in a patient without concomitant systemic disorders, the diagnosis of Gutkafacies is highly likely.…”
Section: Discussionmentioning
confidence: 99%